No Useless Mouth : Waging War and Fighting Hunger in the American Revolution - Herrmann, Rachel B. (Book collections on Project MUSE., 2019)
"Argues that Native American and formerly enslaved communities lost the fight against hunger because white officials in the United States, Nova Scotia, and Sierra Leone curtailed the abilities of men and women to fight hunger on their own terms"--